Comorbidity of ketamine dependence with major depressive disorder increases the vulnerability to neuroaxonal pathology. (February 2023) - Huang, Ming-Chyi; Chen, Chun-Hsin; Liu, Tung-Hsia; Chung, An-Nie; Liu, Yu-Li; Quednow, Boris B.; Bavato, Francesco
Abstract: We recently demonstrated that patients with ketamine dependence (KD) have increased serum levels of neurofilament light chain (NfL), a novel marker of active neuroaxonal pathology, with NfL levels being significantly higher in those KD patients comorbid with major depressive disorder (MDD). However, considering that NfL elevation has been associated with both ketamine-related brain pathology and MDD, we could not determine whether the observed elevation of NfL levels was driven by an interaction of KD with MDD or by MDD itself. Therefore, we compared serum NfL levels between 35 patients with MDD without ketamine use (MDD group), 23 with KD without MDD (KD without MDD group), 30 KD with MDD (KD with MDD group), and 86 healthy controls (HC group). Using a 2*2 (KD*MDD) generalized linear model controlling for age, sex, body mass index, and smoking status, we found that KD and KD*MDD interactions, but not MDD factor, significantly affected NfL levels. Posthoc tests showed that the KD with MDD group had significantly higher NfL levels than all other groups. The KD without MDD group also showed higher NfL levels than the MDD and, as shown before, HC groups. The levels in MDD group were not different from the HC group. These results suggest that the interaction of KD with MDD, but not MDD alone, results in increased vulnerability to neuroaxonal pathology.